Long term variability of Cygnus X-1: VIII. A spectral-timing look at low energies with NICER - König, Ole; Mastroserio, Guglielmo; Dauser, Thomas; Méndez, Mariano; Wang, Jingyi; García, Javier A.; Steiner, James F.; Pottschmidt, Katja; Ballhausen, Ralf; Connors, Riley; García, Federico; Grinberg, Victoria; et al. (Astronomy & Astrophysics, 2024)
The Neutron Star Interior Composition Explorer (NICER) monitoring campaign of Cyg X-1 allows us to study its spectral-timing behavior at energies < 1 keV across all states. The hard state power spectrum can be decomposed into two main broad Lorentzians with a transition at around 1 Hz. The lower-frequency Lorentzian is the dominant component at low energies. The higher-frequency Lorentzian begins to contribute significantly to the variability above 1.5 keV and dominates at high energies. We show that the low- and high-frequency Lorentzians likely represent individual physical processes. The lower-frequency Lorentzian can be associated with a (possibly Comptonized) disk component, while the higher-frequency Lorentzian is clearly associated with the Comptonizing plasma. At the transition of these components, we discover a low-energy timing phenomenon characterized by an abrupt lag change of hard (≳2 keV) with respect to soft (≲1.5 keV) photons, accompanied by a drop in coherence, and a reduction in amplitude of the second broad Lorentzian. The frequency of the phenomenon increases with the frequencies of the Lorentzians as the source softens and cannot be seen when the power spectrum is single-humped. A comparison to transient low-mass X-ray binaries shows that this feature does not only appear in Cyg X-1, but that it is a general property of accreting black hole binaries. In Cyg X-1, we find that the variability at low and high energies is overall highly coherent in the hard and intermediate states. The high coherence shows that there is a process at work which links the variability, suggesting a physical connection between the accretion disk and Comptonizing plasma. This process fundamentally changes in the soft state, where strong red noise at high energies is incoherent to the variability at low energies.
CRIS-Team Scopus Importer:2024-08-02
Keywords: Accretion; Accretion disks; Stars: black holes; Stars: individual: Cyg X-1; X-rays: binaries